Dating the Construction Project of the Church of the Annunciation in Svetvinčenat (Istria) - Musina, Renata I. (Actual Problems of Theory and History of Art, 2023)
The article deals with the history of the Renaissance Annunciation church in the Istrian settlement of Svetvinčenat (Croatia). This church was built as a part of the ambitious urban planning project of the Venetian nobleman Marco Morosini. According to his testament of 1492, the feudal castle with nearby lands was to turn into a self-sufficient city. The building process timeline of the church, as well as of the entire ensemble, has long been controversial. A number of archival documents discovered in the 2010s clarified the constructional stages of the church, but did not explain its architectural features. The article considers the church in Svetvinčenat as one of the churches with a trilobe facade, which were spread mainly on the territory of the Venetian Republic in the 15th – first third of the 16th centuries. On the basis of the compositional analysis of the interior and the facade of the church and surviving written sources, the author seeks to prove that the architectural project of this church dates back to the late 15th century and was influenced by the Venetian Church of Santi Giobbe e Bernardino. This finding not only allows us to take a fresh look at the provincial architectural monument in Istria, but it can also contribute to the reconstruction of the authentic appearance of Santi Giobbe e Bernardino in Venice, which was lost during the later reconstructions.
Keywords: architecture of the Venetian Republic; Croatian architecture; Renaissance architecture in Istria and Dalmatia; trilobe façades; church architecture